FORGET IN THE QUR'AN PERSPECTIVE - Zamakhsyari Bin Hasballah Thaib (Almufida : Jurnal Ilmu-Ilmu Keislaman, 2020)
This paper discusses forgetting from the perspective of the Qur'an. In the Qur'an, the term is used to denote two meanings; First, Nissan means tark, which is to leave. And second, Nissan or forget that applies to those who do not maintain and preserve what they remember so that it disappears. Forgetting is an impossible trait for God. The Prophets, as human beings, are not free from forgetfulness. However, the forgetfulness of the Prophets was not in a context that could neglect their responsibility for delivering the treatise. Prophet Adam, Moses, and Prophet Muhammad are among the Prophets whose narrations are forgotten in the Qur'an. This study was conducted using the thematic method. And among the main conclusions in this study; In the Qur'an, several forms of forgetfulness are mentioned, including the forgetfulness of the Servant to Allah and himself, the forgetfulness of the Servant to the signs of God's greatness, the forgetfulness of the Servant to God's promises, and the forgetfulness of the Servant to the hereafter. Besides, among the factors that cause forgetfulness according to the Qur'an are controlled by Shaytan, and take refuge in Creatures and not only to Allah alone. Therefore, Allah has guided us that the only remedy when forgetting is to hurry to remember God, then pray to ask God not to take responsibility for that forgetfulness.